Internet based intervention (Emotion Regulation Individual Therapy for Adolescents) as add‐on to treatment as usual versus treatment as usual for non‐suicidal self‐injury in adolescent outpatients: The TEENS randomised feasibility trial - Britt Morthorst; Markus Harboe Olsen; Janus Christian Jakobsen; Jane Lindschou; Christian Gluud; Michella Heinrichsen; Bo Møhl; Lotte Rubæk; Olivia Ojala; Clara Hellner; Johan Bjureberg; Anne Katrine Pagsberg (Wiley, 2022)
Abstract Background Non‐suicidal self‐injury (NSSI) is common in adolescents receiving psychiatric treatment and is a significant risk factor for suicidal behavior. There are few randomised clinical trials assessing interventions for NSSI in youth, and knowledge about internet‐delivered interventions is limited. Objective We assessed the feasibility of Internet based Emotion Regulation Individual Therapy for Adolescents (ERITA) in psychiatric outpatients aged 13-17 years who engaged in NSSI. Method A randomised clinical feasibility trial with a parallel group design. Non‐suicidal self‐injury engaging patients were recruited from Child and Adolescent Mental Health Outpatient Services in the Capital Region of Denmark from May to October 2020. ERITA was provided as add‐on to treatment as usual (TAU). ERITA is a therapist‐guided, internet‐based program of emotion regulation and skills training involving a parent. The control intervention was TAU. Feasibility outcomes were the proportion who completed follow‐up interviews at end of intervention; proportion of eligible patients who participated in the trial; proportion of participants completing ERITA. We further investigated relevant exploratory outcomes, including adverse risk‐related events. Results We included 30 adolescent participants, 15 in each group (ERITA vs. Treatment as usual). 90% (95% CI, 72%-97%) of the participants completed post‐treatment interviews; 54% (95% CI, 40%-67%) of the eligible participants were included and randomised; and 87% (95% CI, 58%-98%) of the participants completed at least six out of 11 ERITA modules. We identified no difference for the primary exploratory clinical outcome of NSSI between the two groups. Conclusion There are few randomised clinical trials assessing interventions for NSSI in youth, and knowledge about internet‐delivered interventions is limited. Based on our results we conclude that a large‐scale trial seems feasible and warranted.